Factors Influencing Consumer Adoption of New Technological Products: An Analytical Review of Technology Adoption Theories and Models (Journal of Informatics Education and Research, 2025)
This study aimed to identify the factors that play a role in influencing individuals’ decisions to accept or reject any technology introduced to the market, thereby helping the responsible for marketing these technologies to increase the chances of their adoption by consumers. Accordingly, the study examined – through four main axes – the most important theories and models that have addressed the issue of technology adoption. The study concluded that the most significant factors are performance expectancy, effort expectancy, social influence, and facilitating conditions, as these factors appear in most theories. In addition, the factors of perceived trust and perceived risk have gained considerable attention recently and cannot be neglected in the technological environment.